Quantification of the Total Protein Content of Some Wild Edible Plants Used by the Local People of Kangchup Area, Senapati District of Manipur, India - Kikim, A.; Singh, O. Noyon; Niranjan, Ch. (International Journal of Bio-resource and Stress Management, 2025)
The experiment was conducted during March, 2023 to November, 2024 at the Laboratory of Institutional Biotech Hub, Lilong Haoreibi College, Lilong, Manipur, India to explore various plant protein sources, with traditionally edible plants recognized as rich in protein and widely used by many communities for sustenance. This study analyzed the total protein content in 21 plant species from four categories: trees, shrubs, herbs and creepers, using Lowry’s estimation method with Bovine Serum Albumin (BSA) as a standard. All the proteins were extracted by using phosphate buffer (pH 7.4). Results showed that the highest protein content among trees was found in Wendlandia grandis flower (209.71±3.66 mg g-1 of dry weight) and the lowest in Albizia myriophylla bark (12.00±3.34 mg g-1 of dry weight). Curcuma caesia rhizome contained the highest protein among herbs (108.57±0.48 mg g-1of dry weight), while Alpina officinarum leaves had the lowest (14.86±0.86 mg g-1 of dry weight). In shrubs, Zanthoxylum oxyphyllum leaves exhibited the highest protein content (181.43±2.24 mg g-1 of dry weight), and Smallanthuss onchifolius tubers had the lowest (28.00±0.83 mg g-1 of dry weight). Among creepers, Paederia foetida galls showed the highest protein content (45.14±0.39 mg g-1 of dry weight), while Hodgsonia heteroclita fruit had the lowest (20.29±1.19 mg g-1 of dry weight).